Non‐thermal ablation of non‐neoplastic Barrett's esophagus with the novel EndoRotor® resection device. Issue 5 (1st June 2018) - Knabe, Mate; Blößer, Sandra; Wetzka, Jens; Ell, Christian; May, Andrea
Abstract : Background: International guidelines suggest endoscopic resection for all patients with low‐risk mucosal cancer. Ultimately, it is essential to treat the remaining Barrett's esophagus as part of the treatment. Different thermal ablative therapies have been implemented to effect this treatment. They can lead to potential post‐therapeutic stenosis. Furthermore, a histologic assessment of treated mucosa is not possible. Objective: Clinical evaluation of a novel, non‐thermal resection device (EndoRotor®) in the treatment of non‐neoplastic Barrett's esophagus was conducted. Methods: Fourteen patients with early Barrett's carcinoma were treated with endoscopic resection. Subsequently, EndoRotor® therapy was performed for resection of the remaining Barrett's mucosa. Complications were assessed during the study. After a three‐month period patients received follow‐up endoscopy to evaluate post‐therapeutic stenosis. Results: On average, 674 mm 2 (172 mm 2 – 1600 mm 2 ) of Barrett's mucosa was treated with the novel device. In six (37.5%) cases, intra‐procedural bleeding occurred with the need for hemostasis. All bleeding could be managed by endoscopic therapy alone. After a three‐month follow‐up there was no post‐therapeutic stenosis registered. Conclusion: EndoRotor® resection is a feasible non‐thermal treatment of non‐neoplastic Barrett's esophagus. Larger trials have to evaluate risks and benefits of this novel device.